TQM MENGGUNAKAN SIKLUS DEMING DENGAN METODE KONTRAKTUAL SEBAGAI UPAYA PENINGKATAN KARAKTER SISWA - Kusumawati, Hanifah (Jurnal Ekonomi, 2017)
This study aims to improve the character of student from elementary school through TQM implementation using the Deming cycle with contractual method. The type of this study is action research of school. The research activities carried out by applying the Deming cycle consists of four steps, that is Plan, Do, Check, and Act. The study lasted for two cycles. Data collected by interview and analyzed using descriptive comparative analysis. Obtaining quantitative data described in narrative form, is then performed comparison data to see an increase in the student's character. The findings of the research showed an increased the character of students by 23% in grade 2 and 20% in grade 5.